Diseño de una preparación farmacéutica: gel con actividad antiflamatoria a partir de un extracto obtenido de las partes aéreas de portulaca oleracea verdolaga. - Guzman Heras, Lidia Elizabeth (2015)
Portulaca oleracea verdolaga is used traditionally to reduce the pain caused by inflamation asociated to musculoskeletal diseasses. The current research project has the target of design a pharmaceutical form of gel with antiinflammatory activity from 95 for center ethanolic extract by the use of aerial parts of Portulaca oleracea verdolaga.